Synthesis and Characterization of UV Crosslinkable and Highly Sulfonated Block Copolymer by Living Radical Polymerization - Baek, Kyung-Youl (TAYLOR & FRANCIS LTD, 2010)
UV crosslinkable sulfonated block copolymers of neopentyl p-styrene sulfonate (NSS) and 2-cinnamoylethyl acrylate (CEA) were synthesized by living radical polymerization. For this, the block copolymers of 2-(trimethylsilyl) ethyl acrylate (TMSEA) and NSS were first synthesized by sequential CuBr catalyzed living radical polymerization with 2-bromopropionate (EBP) initiator and N, N, N', N'-pentamethylethyleneamine (PMDETA) ligand. Obtained well defined block copolymers (polydispersity <1.21) were then hydrolyzed with an acid to give the block copolymer of 2-hydroxylethyl acrylate (HEA) and NSS. Cinnamoyl chloride as a crosslinking moiety reacted with the hydrolyzed block copolymers to give final UV crosslinkable sulfonated block copolymers. Theses block copolymers were successfully crosslinked under UV irradiation and generated sulfonic acid groups by thermolysis of the PNSS.
Keywords: MEMBRANES